2018
DOI: 10.1002/jsfa.9386
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ proteomics reveals changes in the lettuce (Lactuca sativa L. Grand Rapid) proteome related to colour and senescence under modified atmosphere packaging

Abstract: BACKGROUND This study used the isobaric tags for relative and absolute quantitation (iTRAQ) technique to determine the effects of active modified atmosphere packaging (MAP) on the modulation of lettuce (Lactuca sativa L. Grand Rapid) colour and senescence. Lettuces, treated or not treated (control) with MAP, were placed in a refrigerator (4 °C, 90–95% relative humidity) for analysis at 3‐day intervals until the ninth day. RESULTS MAP treatment could suppress weight loss, loss of green colour and brittleness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…β-carotene is a pro-vitamin A lipophilic molecule with important biological functions related to antioxidant activity, providing protection to human organism against cancer, cardiovascular diseases and diabetes by scavenging the oxygen free radicals [43]. As the major carotenoid in the pulp of 'Tommy Atkins' mangoes [44], β-carotene was quantified in our study to determine changes in fruit ripening.…”
Section: Discussionmentioning
confidence: 99%
“…β-carotene is a pro-vitamin A lipophilic molecule with important biological functions related to antioxidant activity, providing protection to human organism against cancer, cardiovascular diseases and diabetes by scavenging the oxygen free radicals [43]. As the major carotenoid in the pulp of 'Tommy Atkins' mangoes [44], β-carotene was quantified in our study to determine changes in fruit ripening.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 7B, the MAP groups successfully curtailed the rapid increase in MDA content with respect to the CK group (p < 0.05). Chen et al [44] also found that MAP inhibited chlorophyll degradation and chloroplast destruction, thereby maintaining the green color of lettuce, by blocking MDA production. ROS induction plays a major role in enhancing MDA content [45].…”
Section: Changes In Asa Content and Mda Contentmentioning
confidence: 96%
“…The proportions of MAP gases for selected products are listed in Table 5. 145,146,148,150,[153][154][155][156][157][158][159][160] It can be seen that different foods require different gas compositions, and N 2 , O 2 , and CO 2 are the most commonly used gases for MAP.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
“…MAP resulted in a longer shelf life; quality and safety of the fillets were well maintained. The proportions of MAP gases for selected products are listed in Table 5 145,146,148,150,153–160 . It can be seen that different foods require different gas compositions, and N 2 , O 2 , and CO 2 are the most commonly used gases for MAP.…”
Section: Modified‐atmosphere Packaging and Coating Technologiesmentioning
confidence: 99%